Trust Drivers and Revisit Intention of Foreign Tourists in Bali - Ardani, Wayan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Previous studies on the consequences of trust on revisit intention have been carried out both at service companies and modern retailers, but how it affects tourists rvisit intention at traditional market has not been widely carried out. This study aims to explain the factors that influence trust as well as its consequences on revisit intention of tourists at souvenir traditional market in Bali. In addition, it also explained the role of trust to mediate the effect service quality and product quality towards tourist revisit intention. A survey was conducted from foreign tourists who visited and experienced to shop souvenirs at the traditional market in Bali. The data were analyzed using the SEM-PLS approach. This study revealed that service quality had a positive and significant effect on trust and revisit intention, product quality had a positive and significant effect on trust and revisit intention, trust partially mediated the effect of service quality towards revisit intention and the effect of product quality towards revisit intention. The important factors in creating tourists trust and increasing tourist revisit intention are the ability to maintain consistency of service quality and product quality. This research is expected to prove the importance of trust to shape tourists behaviours, especially revisit intention to souvenir traditional market.